The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.jcrs.2012.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dry-eye disease severity after laser in situ keratomileusis and laser-assisted subepithelial keratectomy

Abstract: There were no significant differences in dry-eye disease markers or tear osmolarity between LASIK and LASEK patients at any stage after surgery up to 1 year. Although tear osmolarity remains one of the highest predictive tests of dry eye, it is complementary with other diagnostic criteria in the context of dry eye after refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…[22][23][24] Prior studies have used the Ocular Surface Disease Index (OSDI) to assess subjective dry eye symptoms (ocular symptoms, visionrelated functions, and environmental triggers) and found increased postoperative scores up to 3 months after surgery, gradually decreasing thereafter. [25][26][27] Questions related to ocular symptoms in the OSDI were almost similar to those from our study (light sensitivity, gritty sensation, eye discomfort, blurring, and fluctuations in vision). Because we aimed to describe the severity and development of the postoperative visual symptoms, we chose to evaluate each symptom with one individual score instead of using an overall score for the visual quality.…”
Section: Discussionsupporting
confidence: 71%
“…[22][23][24] Prior studies have used the Ocular Surface Disease Index (OSDI) to assess subjective dry eye symptoms (ocular symptoms, visionrelated functions, and environmental triggers) and found increased postoperative scores up to 3 months after surgery, gradually decreasing thereafter. [25][26][27] Questions related to ocular symptoms in the OSDI were almost similar to those from our study (light sensitivity, gritty sensation, eye discomfort, blurring, and fluctuations in vision). Because we aimed to describe the severity and development of the postoperative visual symptoms, we chose to evaluate each symptom with one individual score instead of using an overall score for the visual quality.…”
Section: Discussionsupporting
confidence: 71%
“…One study reported osmolarity greater than 308mOsm/L in 30% at 12 months after LASIK. 21 De Paiva et al found that dry eye was associated with preoperative myopia and ablation depth at 6 months after surgery, possibly because of nerves needing to regenerate a longer distance in the case of deeper ablation depth. 20 We did not find correlation between pre-MRSE and Osmolarity in the LVC group.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,19,20 It is believed to resolve in most cases within the first postoperative year, but other studies have shown higher osmolarity 12 months after LASIK and that nerve regeneration may not be complete at 18 months. 14,16,18,21 The majority of articles documenting dry eye after laser vision correction (LVC) surgery include only a limited time of observation after surgery. To the best of our knowledge, there are no studies evaluating dry eye as long as 5 years or more after refractive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…27 Although the severity is milder than LASIK, LASEK surgery also leads to a decreased corneal sensitivity accompanied by changes in tear film function. 28 After LASEK, ocular irritation symptoms developed, and tear film BUT and Schirmer test values were reduced in the early postoperative period. 29 Conventional treatment for postrefractive surgery dry eye includes artificial tears, punctal plug, and serum eye drops.…”
Section: Discussionmentioning
confidence: 99%